Structural instability of the rutile compounds and its relevance to the metal–insulator transition of VO2. (May 2015) - Hiroi, Zenji
Abstract: The metal–insulator transition (MIT) of VO2 is discussed with particular emphasis on the structural instability of the rutile compounds toward dimerization. Ti substitution experiments reveal that the MIT is robust up to 20% Ti substitutions and occurs even in extremely thin V-rich lamellas in spinodally decomposed TiO2 –VO2 composites, indicating that the MIT is insensitive to hole doping and essentially takes on a local character. These observations suggest that either electron correlation in the Mott–Hubbard sense or Peierls (Fermi-surface) instability plays a minor role on the MIT. Through a broad perspective of crystal chemistry on the rutile-related compounds, it is noted that VO2 and another MIT compound NbO2 in the family eventually lie just near the borderline between the two structural groups with the regular rutile structure and the distorted structures characterized by the formation of dimers with direct metal–metal bonding. It is also shown that the two compounds of the rutile form do not follow the general trends in structure observed for the other rutile compounds, giving clear evidence of an inherent structural instability present in the two compounds. The MITs of VO2 and NbO2 are natural consequences of structural transitions between the two groups, as all the d electrons are trapped in the bonding molecular orbitals of dimers at low temperatures. Such dimer crystals are ubiquitously found in early transition metal compounds having chain-like structures, such as MoBr3, NbCl4, Ti4 O7, and V4 O7, the latter two of which also exhibit MITs probably of the same origin. In a broader sense, the dimer crystal is a kind of "molecular orbital crystals" in which virtual molecules made of transition metal atoms with partially-filled t 2 g shells, such as dimers, trimers or larger ones, are generated by metal–metal bonding and are embedded into edge- or face-sharing octahedron networks of various kinds. The molecular orbital crystallization opens a natural route to stabilization of unpaired t 2 g electrons in crystals.